Abundant extraterrestrial amino acids in the primitive CM carbonaceous chondrite Asuka 12236. (20th August 2020) - Glavin, Daniel P.; M Lain, Hannah L.; Dworkin, Jason P.; Parker, Eric T.; Elsila, Jamie E.; Aponte, José C.; Simkus, Danielle N.; Pozarycki, Chad I.; Graham, Heather V.; Nittler, Larry R.; Alexander, Conel M.O'D.
Abstract: The Asuka (A)‐12236 meteorite has recently been classified as a CM carbonaceous chondrite of petrologic type 3.0/2.9 and is among the most primitive CM meteorites studied to date. Here, we report the concentrations, relative distributions, and enantiomeric ratios of amino acids in water extracts of the A‐12236 meteorite and another primitive CM chondrite Elephant Moraine (EET) 96029 (CM2.7) determined by ultra‐high‐performance liquid chromatography time‐of‐flight mass spectrometry. EET 96029 was highly depleted in amino acids and dominated by glycine, while a wide diversity of two‐ to six‐carbon aliphatic primary amino acids were identified in A‐12236, which had a total amino acid abundance of 360 ± 18 nmol g −1, with most amino acids present without hydrolysis (free). The amino acid concentrations of A‐12236 were double those previously measured in the CM2.7 Paris meteorite, consistent with A‐12236 being a highly primitive and unheated CM chondrite. The high relative abundance of α‐amino acids in A‐12236 is consistent with formation by a Strecker‐cyanohydrin dominated synthesis during a limited early aqueous alteration phase on the CM meteorite parent body. The presence of predominantly free glycine, a near racemic mixture of alanine (d /l ~0.93–0.96), and elevated abundances of several terrestrially rare non‐protein amino acids including α‐aminoisobutyric acid (α‐AIB) and racemic isovaline indicate that these amino acids in A‐12236 are extraterrestrial in origin. Given a lack of evidence for biological amino acid contamination in A‐12236, it is possible that some of the l ‐enantiomeric excesses (l ee ~34–64%) of the protein amino acids, aspartic and glutamic acids and serine, are indigenous to the meteorite; however, isotopic measurements are needed for confirmation. In contrast to more aqueously altered CMs of petrologic types ≤2.5, no l ‐isovaline excesses were detected in A‐12236. This observation strengthens the hypothesis that extensive parent body aqueous activity is required to produce or amplify the large l ‐isovaline excesses that cannot be explained solely by exposure to circularly polarized radiation or other chiral symmetry breaking mechanisms prior to incorporation into the asteroid parent body.